The early modern Hispanic world : transnational and interdisciplinary approaches - Lynn, Kimberly; Rowe, Erin Kathleen, 1974- (Cambridge, United Kingdom : Cambridge University Press, 2017)
"Iberia stands at the center of key trends in Atlantic and world histories, largely because Portugal and Spain were the first European kingdoms to 'go global.' The Early Modern Hispanic World engages with new ways of thinking about the early modern Hispanic past, as a field of study that has grown exponentially in recent years. It focuses predominantly on questions of how people understood the rapidly changing world in which they lived--how they defined, visualized, and constructed communities from family and city to kingdom and empire. To do so, it incorporates voices from across the Hispanic World and across disciplines. The volume considers the dynamic relationships between circulation and fixedness, space and place, and how new methodologies are reshaping global history, and Spain's place in it"--
Introduction: mapping the early modern Hispanic world / Kimberly Lynn and Erin Kathleen Rowe -- Part I. City and society -- Towns and the forging of the Spanish Caribbean / Ida Altman -- The walk of the town: modeling the early modern city / James S. Amelang -- The king, the city, and the saints: performing sacred kingship in the royal capital / Erin Kathleen Rowe -- Part II. Religion, race, and community -- A minority within a minority: the new and old Jewish converts of Sigüenza, 1492-1570 / Sara Tilghman Nalle -- On the Alumbrados: confessionalism and religious dissidence in the Iberian world / Mercedes García-Arenal and Felipe Pereda -- The Spanish encounter with Islam / Benjamin Ehlers -- From peasants to slave owners: race, class, and gender in the Spanish Empire / Allyson M. Poska -- Part III. Law and letters -- On early modern science in Spain / María M. Portuondo -- Spanish inquisitors, print, and the problem of publication / Kimberly Lynn -- "An immense structure of errors": Dionisio Bonfant, Lucas Holstenius, and the writing of sacred history in seventeenth-century Sardinia / A. Katie Harris -- The forces of the king: the generation that read Botero in Spain / Xavier Gil -- Part IV. Performance and place -- Censuring public images: a woodcut in the inquisition trial of Esteban Jamete / Fernando Marías -- Epic temptation: Lope de Vega's Battle of Lepanto / Elizabeth R. Wright -- Staging femininity in early modern Spain / Marta V. Vicente -- Conclusion: the history of early modern Spain in retrospect / John Elliott.
Includes bibliographical references and index.
Keywords: 1385-1799; Social change -- Portugal -- Historiography; Social change -- Spain -- Historiography; Historiography; Portuguese colonies; Social change -- Historiography; Social history -- Historiography; Spanish colonies; Portugal -- Colonies -- Historiography; Portugal -- History -- Modern, 1580- -- Historiography; Portugal -- History -- Period of discoveries, 1385-1580 -- Historiography; Portugal -- Social conditions -- Historiography; Spain -- Colonies -- Historiography; Spain -- History -- 18th century -- Historiography; Spain -- History -- House of Austria, 1516-1700 -- Historiography; Spain -- Social conditions -- Historiography; Portugal; Spain; History